Imprisonment Today
IX, 204 p.
Keywords: A collection of papers on various aspects of the imprisonment process in which each chapter highlights a critical area in the prisoner's passage through the penal system. The book aims to promote a greater understanding of the issues and problems inherent to the British penal system.